The entrepreneurial character of the library profession - Gómez-Hernández, José-Antonio (Anuario ThinkEPI, 2008)
We believe that librarians have a proactive attitude to give better services to their users, and to have a specific role in the present social context characterized by an enormous cultural and informative offer. To justify this opinion we describe good practices and experiences of the Spanish public libraries.